Membangun Semangat Tim dan Dinamika Penguatan dalam Manajemen Perubahan - Apriyenti, Apriyenti; Oktawira, Leni; Mudarti, Hasni; Fazis, M. (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the potential to strengthen team spirit and internal dynamics in supporting organizational change management. The approach used is a literature review, with data collection techniques through systematic searches across various databases, such as Google Scholar. Data analysis is conducted qualitatively through a descriptive-analytical approach. The research results indicate that change management requires a holistic approach, encompassing team spirit enhancement, conflict and stress management, creativity development, and active participation from all elements of the organization. The formation of an inclusive, flexible, and innovative organizational culture is a key factor in turning change into a strategic opportunity to improve performance and organizational sustainability